A preliminary study of corporate stress and the female Filipino executives - Estalilla, Cynthia O. (Animo Repository, 1989)
The second half of the twentieth century saw the rapid growth in the emerging issues on women worldwide. Such emphasis provided the impetus for numerous researches, studies and articles to proliferate. All of these tackled various aspects of womanhood. And yet, the onset of the 21st century does not seem to augur the waning of women issues. And it is in this light that the present study was undertaken. This study attempted to surface the perceptions of 20 Filipino female executives concerning the nature, causes and effects of corporate stress in their professional work, and tried to determine the stress-coping mechanisms employed by these Filipinas in their work situations. The highlights of the study are as follows: Half of the respondents were single who were between 30 to 39 years old, and who have been with their companies for at least five years earning about P250,000 annually. They perceived corporate stress as that which is linked to work overload due to the critical corporate role of the respondent in the business organization. It was perceived as rooted on unreasonable demands from top management and heavy workload without adequate support staff. This type of stress falls under the quantitative overload expounded by Schultz & Schultz (1986) which is the condition of having too much work to do in the time available (for it to be accomplished). Based on the Stress Diagnostic Survey, the major causes of corporate stress were perceived to be mainly intrinsic to their job , i.e., meeting deadlines, time constraints, heavy workload/unreasonable demands, inadequate support from management, inadequate or poor performance of subordinates, and operational problems. This perception validated the results of an earlier study of Cooper and Marshall (1978) which identified sources of stress in the workplace as intrinsic to the job, the role in the organization, relationships at work...organizational structure and climate... (pp. 159-163). There were both negative and positive effects of corporate stress on performance: increased productivity and efficiency on the one hand, and lower quality output or performance, increase in the likelihood to commit mistakes, and diminished enthusiasm for the job, on the other hand. In coping with corporate stress, the respondents tended to rely on self-care coping mechanisms such as praying or meditating, exercise and recreation. Hans Selye (1983) theorized the human response to coping with stress as the general adaptation syndrome (p. 109). Since this study was primarily conducted using female corporate respondents, it would be interesting to find out the difference and similarities of perceptions of corporate stress between the male and female corporate executives. With regard to the coping mechanisms which can be adopted by the management to help reduce corporate stress, self-care coping options can be developed as a matter of corporate policy. Moreover, since the Filipinos are introspective and religious by nature, praying or meditating was cited as one way to reduce stress, a company may want to provide a place of tranquility where all employees, including executives, can pray and meditate at peace. The potential rewards of an executive position are power, challenge, fulfillment, status and money - but so are the corporate stresses that come with the position. To give her best corporate performance, the Filipino female executive needs to effectively manage job stress.